Reading comprehension in students from first to third grade with “Escuela Nueva” methodology - Ávila Cepeda, Hugo Alfonso; Jiménez Pinzón, Rosalbina; Torres Ortiz, Jaime Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The General Education Law (1994) establishes among the objectives of elementary school, the development of communicative skills to read and understand. Analyzed the results of the “SABER” tests for third grade in language (2014), low reading comprehension performances were observed in students of the San Pablo campus with Escuela Nueva (EN) methodology. For this reason, a didactic action was implemented that complemented the EN guidelines for the improvement of reading skills in students from first to third grade of primary school, taking contributions from authors such as Henao, Coronel, Thorne, Solé, Jolibert, Blythe, among others. For this purpose, the methodology of qualitative researchaction was followed through diagnostic tests, comparative results between the previous tests and implementation of the didactic action, with which better reading performance was obtained in the students by carrying out several activities around reading, being seen the transformation of the pedagogical practice of the teacher.